ANTIOXIDANT ACTIVITY OF CONJUGATED LINOLEIC ACID - B, Lalithadevi; Ns, Muthiah; Murty K, Satya Narayana (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the present study is to evaluate the antioxidant effect of conjugated linoleic acid (CLA). CLA is a collective term for a group of positional and geometric isomers of linoleic acid with conjugated double bond system. CLA is found in milk products and ruminant meat. CLA has been proved to be having many health benefits, one of them one being antioxidant effect. Methods: Various methods are used to find out the antioxidant effect of CLA. They are 1,1- diphenyl-2-picrylhydrazyl free radical scavenging assay, hydroxy radical scavenging assay, nitrous oxide radical scavenging assay, reducing power method, and phosphomolybdenum antioxidant assay. All these methods were done to test the antioxidant activity of CLA. Results: Standards error of mean calculated for all the tests. Statistical analysis done using one-way analysis of variance between the groups and SPSS software version 20 is used. p<0.05 is considered statistically significant. All the tests are statistically significant. Conclusion: As p values for all the tests came significant, and it was concluded that CLA has got antioxidant property. CLA could protect membranes composed of 1-palmitoyl 2-linoleoyl phosphatidylcholine from oxidative modification under conditions of metal ion-dependent or -independent oxidative stress. Finally, it was concluded that CLA has got potential health benefits such as weight reduction, antiaging, and antioxidative properties.